Voices from four directions : contemporary translations of the Native literatures of North America - Swann, Brian (University of Nebraska Press, 2004)
Storytelling and singing continue to be a vital part of community life for Native peoples today. Voices from Four Directions gathers stories and songs from thirty-one Native groups in North America-including the Iñupiaqs in the frigid North, the Lushootseeds along the forested coastline of the far West, the Catawbas in the humid South, and the Maliseets of the rugged woods of the East. Vivid stories of cosmological origins and transformation, historical events remembered and retold, as well as legendary fables can be found in these pages. Well-known Trickster figures like Raven, Rabbit, and Coyote figure prominently in several tales as do heroes of local fame such as Tom Laporte of the Maliseets. The stories and songs entertain, instruct, and recall rich legacies as well as obligations. Many are retellings and reinventions of classic narratives, while others are more recent creations.